Generation of 2D and 3D quasicrystalline structures using the projection method - Milas, Peker. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
Two algorithms for generating 2D and 3D quasiperiodic lattices by the strip projection method are presented. For the 2D algorithm a 5D simple cubic integral lattice with unit lattice constant is used as root lattice with a rhombic icosahedron as the projection window. For the 3D case a 6D simple cubic integral lattice with unit lattice constant is used as root lattice with a rhombic triacontahedron as the projection window.
Keywords: Quasicrystals.; Crystallography, Mathematical.